Protective Effects of Dipterocarpus tuberculatus in Blue Light-Induced Macular Degeneration in A2E-Laden ARPE19 Cells and Retina of Balb/c Mice - Su Jin Lee; Yu Jeong Roh; Ji Eun Kim; You Jeong Jin; Hee Jin Song; Ayun Seol; So Hae Park; Bounleuane Douangdeuane; Onevilay Souliya; Sun Il Choi; Dae Youn Hwang (MDPI AG, 2023)
Natural products with significant antioxidant activity have been receiving attention as one of the treatment strategies to prevent age-related macular degeneration (AMD). Reactive oxygen intermediates (ROI) including oxo-N-retinylidene-N-retinylethanolamine (oxo-A2E) and singlet oxygen-induced damage, are believed to be one of the major causes of the development of AMD. To investigate the therapeutic effects of methanol extracts of Dipterocarpus tuberculatus Roxb. (MED) against blue light (BL)-caused macular degeneration, alterations in the antioxidant activity, apoptosis pathway, neovascularization, inflammatory response, and retinal degeneration were analyzed in A2E-laden ARPE19 cells and Balb/c mice after exposure of BL. Seven bioactive components, including 2α-hydroxyursolic acid, ε-viniferin, asiatic acid, bergenin, ellagic acid, gallic acid and oleanolic acid, were detected in MED. MED exhibited high DPPH and ABTS free radical scavenging activity. BL-induced increases in intracellular reactive oxygen species (ROS) production and nitric oxide (NO) concentration were suppressed by MED treatment. A significant recovery of antioxidant capacity by an increase in superoxide dismutase enzyme (SOD) activity, SOD expression levels, and nuclear factor erythroid 2-related factor 2 (NRF2) expression were detected as results of MED treatment effects. The activation of the apoptosis pathway, the expression of neovascular proteins, cyclooxygenase-2 (COX-2)-induced inducible nitric oxide synthase (iNOS) mediated pathway, inflammasome activation, and expression of inflammatory cytokines was remarkably inhibited in the MED treated group compared to the Vehicle-treated group in the AMD cell model. Furthermore, MED displayed protective effects in BL-induced retinal degeneration through improvement in the thickness of the whole retina, outer nuclear layer (ONL), inner nuclear layer (INL), and photoreceptor layer (PL) in Balb/c mice. Taken together, these results indicate that MED exhibits protective effects in BL-induced retinal degeneration and has the potential in the future to be developed as a treatment option for dry AMD with atrophy of retinal pigment epithelial (RPE) cells.